Characteristics of igneous rocks and their significance in hydrocarbon accumulation in Block C of Santos Basin, SE Brazil - Jian Zhao; Jie Zhang; Junfeng Zhao; Kangxu Ren; Chaofeng Wang; Yuan Guo (地质科技通报, 2023)
Santos Basin is characterized by multiple phases of magmatic events and widespread distribution of igneous rocks, which have significant affect of hydrocarbon accumulation. Taking Block C of Santos Basin as a typical and representative example, this paper focused on the characteristics of igneous rocks and their roles in hydrocarbon accumulation through the analysis of igneous rock petrology, geochronology, petrogeochemistry, and gas isotopes. In Block C, at least two main stages of magma events were developed: Aptian magma (122.8±0.6-110.8±0.6 Ma) and Santonian-Campanian magma (84.2±0.7-77.4±0.4). The Aptian magma is dominated by eruptive rocks and has experienced dozens of eruptions, accompanied by several layers of subvolcanic rocks. In comparison, Santonian-Campanian magma is distributed in a relatively random pattern. The multipulse eruption of Aptian magma formed an igneous rock-coquinas complex of more than 600 meters in thickness, inducing a local paleohigh in Itapema Formation. This directly caused the trap crest to shift and contributed to the development of high-quality carbonate deposition in Barra Velha Formation. Before the eruption of Aptian magma, the north flank of Block C was paleohigh, where a particular scale of microbial carbonate reservoirs was anticipated to develop in the Barra Velha Formation as well. These carbonate reservoirs were favorable for hydrocarbon accumulation. The later Santonian-Campanian intrusions also impact carbonate reservoirs through hydrothermal fluid circulation and contact metamorphism. Meanwhile, a large amount of associated CO2 accumulated in the trap led to a high GOR (gas oil ratio) and high CO2 content and changed the fluid composition through the extraction process.A CO2 gas reservoir with condensed oil was eventually formed in the current crest in Block C, as proven by drilled well A.Another pool with high CO2 content is also expected in its north flank, to be demonstrated in the future.